The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.21203/rs.3.rs-34757/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors influencing early initiation of breastfeeding among mothers in Rajshahi district, Bangladesh

Abstract: Background: Early initiation of breastfeeding (EIBF) act as the first immunization for the newborns, fortify their immune defense system and eventually reduce the mortality rate. This study aimed to identify the influential factors of EIBF among mothers in Rajshahi district, Bangladesh.Methods: A total number of 421 mothers living in Rajshahi district who had at least one child aged 6-24 months were considered as sample. Mothers were selected using multistage random sampling. This study was conducted from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…27 Another study in the Rajshahi area of Bangladesh found that the prevalence of early breastfeeding beginning was 88.4%, which is remarkably similar to our findings due to the similar sociodemographic profile. 28 Alternatively, a lower rate of moms initiating nursing early and offering breast milk to their child immediately after delivery was observed in various areas of the country, with only 46.9% doing so in Jessore district. 26 The prevalence of EBF (early breast feeding) in this study was below medium range, which is in line with findings of other studies in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another study in the Rajshahi area of Bangladesh found that the prevalence of early breastfeeding beginning was 88.4%, which is remarkably similar to our findings due to the similar sociodemographic profile. 28 Alternatively, a lower rate of moms initiating nursing early and offering breast milk to their child immediately after delivery was observed in various areas of the country, with only 46.9% doing so in Jessore district. 26 The prevalence of EBF (early breast feeding) in this study was below medium range, which is in line with findings of other studies in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%